A qualitative study of physician perspectives of cost-related communication and patients' financial burden with managing chronic disease. Issue 1 (June 2015) - Patel, Minal; Shah, Khooshbu; Shallcross, Meagan
Abstract Background Patient financial burden with chronic disease poses significant health risks, yet it remains outside the scope of clinical visits. Little is known about how physicians perceive their patients' health-related financial burden in the context of primary care. The purpose of this study was to describe physician experiences with patients' financial burden while managing chronic disease and the communication of these issues. Methods In November 2013, four focus groups were conducted in an academic medical center. A convenience sample of 29 internal and family medicine resident physicians was used in this study. A semi-structured interview protocol was employed by trained facilitators. Coded transcripts were analyzed for themes regarding physicians' experiences with identifying, managing, and communicating financial burden with their patients in the context of primary care. Results Major themes identified were 1) patient financial burden with chronic care is visible to physicians, 2) patient's financial burden with chronic care and discussing these issues is important to physicians, 3) ability to identify patients who perceive financial burden is imperfect, 4) communication of financial burden with patients is complex and difficult to navigate, 5) strategies utilized to address concerns are not always generalizable, and 6) physicians have ideas for widespread change to make these conversations easier for them. Conclusion Awareness of physician perspectives in identifying and addressing their patients' disease-related financial burden may better equip researchers and medical educators to develop interventions that aid care teams in better understanding these patient concerns to promote compliance with treatment recommendations.